Breast and Prostate Cancer Survivors’ Experiences of Patient Centered Cancer Follow-Up Care from Primary Care Physicians and Oncologists - Hudson, Shawna V. (J Cancer Surviv, 2016)
PURPOSE: Patient-physician relationships impact health care seeking and preventive screening behaviors among patients. At the end of active treatment some cancer survivors report feeling disconnected from their care team. This study explores cancer survivors’ experiences of patient centered cancer follow-up care provided by primary care physicians (PCP) and oncologists (ONC). METHODS: 305 early stage, breast and prostate cancer survivors at least two years post treatment were surveyed from four community hospital oncology programs in New Jersey. Participants reported receipt of patient centered care measured by care coordination, comprehensiveness of care and personal relationship with PCPs and ONCs. RESULTS: PCPs received higher ratings for coordination of care and comprehensive care than ONCs from all survivors (p<0.01). However, prostate and breast cancer survivors rated strengths of their personal bonds with the physicians differently. While prostate cancer survivors rated PCPs significantly higher for all items (p<0.028), breast cancer survivors rated ONCs significantly higher on four out of seven items including having been through a lot together, understanding what is important regarding health, knowing their medical history and taking their beliefs and wishes into account (p<0.036). CONCLUSIONS: Prostate and breast cancer survivors report different experiences with their PCPs and oncologists around the comprehensiveness and coordination of their cancer follow–up care in addition to the strength of their relationships with their physicians.